Identifying options for the development of sustainable seed systems: Insights from Kenya and Mali - Anja Christinck; Fred Rattunde; Alpha Kergna; Wellington Mulinge; Eva Weltzien (University of Bonn, Center for Development Research (ZEF), 2018)
This paper results from a study that was commissioned to contribute to the Program of Accompanying Research for Agricultural Innovation (PARI)2. The overall purpose was to propose an agenda for supporting sustainable development of seed systems in two Sub-Saharan countries, Kenya and Mali, based on the experiences and insights of seed system actors who contribute to various functions and operate at different scales. The study relied on a mixed methodology, including (1) a desk review of secondary sources; (2) interviews with individual seed system actors and key informants; and (3) workshops in which diverse actors jointly discussed and prioritized options for sustainable seed system development. Staple cereal crops were targeted that are important for the farming and food systems of both countries: maize and sorghum for Kenya and maize, rice, sorghum and pearl millet for Mali. [...]
Keywords: 330; Seed system; human activity system; seed policy; seed system security; actor-orientation